The dead Syrian refugee boy goes viral: funerary Aylan Kurdi memes as tools of mourning and visual reparation in remix culture. (November 2020) - Mielczarek, Natalia
The picture of 3-year-old Syrian refugee Aylan Kurdi, whose dead body washed up on a Turkish beach in September 2015, was lauded as iconic after it went viral. Within hours, Aylan was a symbol, a hashtag and a meme. This project analyzes funerary Aylan memes to understand their meanings and functions as they proliferated in cyberspace. Through iconographic tracking and visual rhetorical analysis, the project expands the functions of memes from visual jokes and social and political commentary to tools of grieving and atonement. The study demonstrates how memes are deployed to subvert and renegotiate reality, in this case to create a 'better ending' for the child and seek reparations for his death. The project also suggests that the rhetorical powers of iconic images may be eroding in remix culture due to their digital appropriations.